Gastric metastasis from high-grade soft tissue sarcoma: a rare occurrence with literature review - Krsteska, Blagica; Angelovska, Tamara; Adem, Xhem; Zdravkovski, Panche; Todorova, Teodora; Samardjiski, Milan; Darko DJambaz; Kostadinova Kunovska, Slavica (Oxford University Press and JSCR Publishing Ltd, 2025)
Metastasis of high-grade soft tissue sarcoma to the stomach is an extremely rare occurrence. While sarcomas can spread to distant organs,they most commonly metastasize to the lungs,liver,and bones.We report a unique case of gastric metastasis from a high-grade soft tissue sarcoma,occurring 4 years after the initial diagnosis of fibrosarcoma in the right femoral region.The patient did not undergo adjuvant chemotherapy and developed a large soft tissue metastasis in the left gluteal region 2 years later. After 4 years, he presented with a second soft tissue metastasis and suspected metastatic lung nodules. Symptoms of melena and severe anemia prompted a gastroscopic examination, which revealed gastric metastasis from a high-grade soft tissue sarcoma. Due to severe anemia, a palliative gastric resection was performed.A review of the literature indicates that metastatic leiomyosarcomas are the most frequently reported sarcoma subtype metastasizing to the stomach.
Keywords: metastasis; sarcoma; pleomorphic; melena; anemia